2015 First Boston Symposium of Encoded Library Platforms. Issue 7 (5th July 2016) - Goodnow Jr., Robert A.; Davie, Christopher P.
Abstract : Guest Editors Robert Goodnow and Christopher Davie recap the first Boston Symposium of Encoded Library Platforms and introduce the MedChemComm web collection on 'DNA Encoded Libraries'.